At Issue: The “Muslims in Ethiopia Complex” and Muslim Identity: The Trilogy of Discourse, Policy, and Identity - Miftah, Mükerrem (University of Florida, 2015)
The “Muslims in Ethiopia complex” envelops three interrelated fundamental dimensions in the relation between Muslims and Ethiopia. The first is viewing it as a discourse among academics in “Ethiopian Studies.” Utilizing the broader rubric of “Hi/storying,”the present article argues that, except for a few lately emerging counteractive discourses, it has largely remained unabated. The second view is that of it as the policy and praxis of many of the ruling elites in Ethiopian history. The article argues that although the expressions of this policy and practice have been changing over time, there are still instances of its continuation as policy to this day. Third, and related closely to the above dimensions, is the view of this complex as the actual marginalized lived experiences and the associated self-perception of Muslims. However, as the unintended outcome of this policy, the article argues for the progressively developing “Ethiopian Muslims” consciousness and identity. It concludes by tracing and examining past and present expressions of the “Ethiopian Muslims” identity.
FSM Vakıf Üniversitesi, Medeniyetler İttifakı Enstitüsü